Platelet Aggregation in Whole Blood - Studies with a Platelet Counting Technique - Methodological Aspects and Some Applications - Falcon, C; Arnout, J; Vermylen, J (Thrombosis and Haemostasis, 1989)
We describe a method for measuring platelet aggregation in whole blood by single platelet counting. The importance of a low stirring speed (100 rpm) to obtain agonist-specific aggregation is stressed. Despite this low stirring speed, the sensitivity to agonists equals that of the turbidometric technique in platelet-rich plasma. The optimal concentration of formaldehyde for fixing the aggregates, the effects of storage times and anticoagulant are studied. Applicability to the study of platelet function inhibitors or of inherited platelet function disorders is illustrated. It is concluded that this technique, used under the appropriate conditions, combines the advantage of measuring platelet aggregation in a more physiologtc environment with the advantages of the turbidometric technique such as high sensitivity.
Keywords: Platelet aggregation, whole blood; Platelet aggregation, platelet counting